STUDI PERILAKU LIKUIFAKSI MENGGUNAKAN DATA TES LABORATORIUM TRIAKSIAL SIKLIS - Marwan
This study describes an application of standard analytical procedures based on laboratory cyclic test results to evaluate the soil liquefaction potential in the field. A soil profile in the area of Lhokseumawe Public Port, North Aceh was selected for investigation. Representative samples of the soil deposit were tested using a standard cyclic triaxial apparatus. The triaxial tests were conducted in accordance to the procedure of Mulilis et al. (1977). Pore-water pressure change evaluation in the sand deposit due to earthquake shaking was based on the analytical procedure proposed by Seed et al. (1976). Results showed that liquefaction would be expected to occur throughout the soil deposit at depths ranging from 0 meter to 7 meters, after about 12 seconds to 52 seconds of shaking. In addition, it was shown that most (or a significant) part of pore pressure dissipation was within less than 45 minutes after the eartquake shaking ceased